PEMBERIAN ABU JERAMI PADI DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max (L.) Merrill) DI LAHAN GAMBUT - Lubis, Nursiani; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to determine the effect of the interaction of chicken manure and ash rice straw on peatlands and get a better dose of growth and yield of soybean. This research was conduct on randomized block design of factorial that consist of two factors. The first factor was the ash rice straw, with 3 levels 0 ton/ha, 3 ton/ha and 6 ton/ha and the second factor was the chicken manure fertilizer with 4 levels of 0 ton/ha, 5 tons/ha, 10 ton/ha and 15 ton/ha. The result showed that the ash rice straw and chicken manure fertilizer significantly effect of rate plant growth and weight 100 seeds, but the effect was not significantly on weight nodule, leaf area index, age of flowering plants, harvesting, the percentage of pods phity, number of seeds per plant, harvest index and seed yield per m2. The highest yield in soybean was obtained on giving of 6 tons/ha ash rice straw and 15 ton/ha of chicken manure fertilizer was 3.22 ton/ha increase of 25.27% of the without treatment, while the giving of ash rice straw 6 ton/ha and chicken manure fertilizer 10 ton/ha was 3.17 ton/ha increase 23.71% of the without treatment and giving of ash rice straw 6 ton/ha and chicken manure fertilizer 5 ton/ha was 3.08 ton/ha increase 20.31% of the without treatment. Keyword: Soybean, Ash rice straw, Chicken manure fertilizer, Peatland.